2002
DOI: 10.1161/hs0202.102601
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cerebral Blood Flow Velocities in Fabry Disease With Reversal After Enzyme Replacement

Abstract: Background and Purpose-Fabry disease is an X-linked inherited disorder resulting from a deficiency of ␣-galactosidase A. Cerebrovascular disease in Fabry disease includes small-vessel disease and larger-vessel ectasia in a predominantly posterior distribution. We assessed transcranial Doppler (TCD) blood flow velocities in naive and enzyme-treated Fabry patients. Methods-TCD was used to noninvasively examine patients with Fabry disease for abnormal cerebral blood flow velocities. TCD measurements were also mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
85
4
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 26 publications
5
85
4
8
Order By: Relevance
“…Other sophisticated studies evaluated the effect of ERT on CNS through the study of regional cerebral blood flow, measured by [ 15 O] H 2 O, positron emission tomography and transcranial Doppler studies 3,14,15 . These studies showed significant improvement in abnormal vascular responses after 18 to 24 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other sophisticated studies evaluated the effect of ERT on CNS through the study of regional cerebral blood flow, measured by [ 15 O] H 2 O, positron emission tomography and transcranial Doppler studies 3,14,15 . These studies showed significant improvement in abnormal vascular responses after 18 to 24 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the deposition of such lipids contributes directly to endothelial dysfunction. The precise relationship between abnormal sphingolipid metabolism and impaired endothelial function is not clear (5). Most of the burden of disease results from a vasculopathy associated with progressive damage of the heart and kidney as well as cerebrovascular strokes.…”
mentioning
confidence: 99%
“…One consequence of NO pathway dysregulation may be cerebral hyperperfusion resulting in altered vascular reactivity and elongation of cerebral blood vessels predominantly in the vertebrobasilar circulation (5). Evidence for excess formation of superoxide or reactive oxygen species (ROS) was provided recently by a magnetic resonance imaging and arterial spin labeling study (7).…”
mentioning
confidence: 99%
“…Enzyme replacement therapy can clear microvascular endothelial deposits of glycosphingolipids from the kidneys, heart and skin in patients with Fabry's disease, reversing the pathogenesis of the chief clinical manifestations of this disease. Although a tendency to normalization of cerebral vessel compliance and regional cerebral hyperperfusion has been shown in patients with the disease after enzyme replacement therapy, 21 beneficial effects of this treatment on the incidence of stroke in Fabry's disease have not yet been shown. Reasons for the failure of enzyme replacement therapy yet to affect stroke incidence in the disease include the irreversible damage done by the time patients develop such late complications.…”
Section: Discussionmentioning
confidence: 99%